2020
DOI: 10.1177/1071100720962398
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Weightbearing Computed Tomography Scan in Hallux Valgus

Abstract: Background: Hyperpronation of the first metatarsal in hallux valgus (HV) is poorly understood by conventional weightbearing radiography. We aimed to evaluate this parameter using weightbearing computed tomography (WBCT) and to understand its association with other standard measurements. Methods: Retrospective evaluation of WBCT and weightbearing radiographs (WBXRs) was performed for 20 patients with HV feet and 20 controls with no such deformity. Axial computed tomography images of both groups were compared fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…The 95% CIs demonstrate that mean normative M1 rotation lies slightly pronated, rather than parallel to a ground reference (Figure 4). However, the relatively wide ranges reported with both methods suggest significant natural variability in M1 rotation, 19 even among feet without clinical/radiographic deformity. Additionally, this study showed that measuring the M1 head lateral edge shape can also give clinicians an estimate of M1 rotation using anteroposterior (AP) radiographs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The 95% CIs demonstrate that mean normative M1 rotation lies slightly pronated, rather than parallel to a ground reference (Figure 4). However, the relatively wide ranges reported with both methods suggest significant natural variability in M1 rotation, 19 even among feet without clinical/radiographic deformity. Additionally, this study showed that measuring the M1 head lateral edge shape can also give clinicians an estimate of M1 rotation using anteroposterior (AP) radiographs.…”
Section: Discussionmentioning
confidence: 94%
“…In the last 10 years, axial rotation of the first metatarsal (M1) in the coronal plane has gained increasing attention as having a clinically meaningful impact in HV deformity. 15,19,43 This rotational deformity is referred to as “pronation” when the plantar aspect of the M1 faces inward, toward the second metatarsal, and “supination” when the plantar aspect of the M1 faces outward, away from the second metatarsal. 10,29,43…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Based on values that are 2 standard deviations higher than the mean, the upper normal limit of MPA can be as high as 30 degrees in hallux valgus, 5,28 and the upper normal limit of the α angle has been reported as high as 33 degrees in hallux valgus. 15,20 Failure to correct coronal rotation may be a cause of recurrent deformity and persistent sesamoid subluxation. 14 Many procedures have been described to supinate the metatarsal in hallux valgus, ranging from proximal osteotomies to modified first tarsometatarsal joint arthrodesis, with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mahmoud et al [33] found that almost half of the subjects in the control group had an abnormal alpha angle greater than 16° (the value below the cut point should be regarded as a normal alpha angle according to Kim's method [34]), indicating that the pronation may also exist in feet without HV. It should be noted that their coronal rotation may be affected by the pronation of the midfoot and hindfoot bones, as it used the ground level and the distal 1 st MT as the measurements reference points.…”
Section: The Site Of Coronal Deformitymentioning
confidence: 99%